(untitled) (Asian Journal of Medical and Biological Research, 2016)
Stocking density is considered one of the important factors affecting fish growth. The study was aimed to compare the growth parameters of monosex tilapia at various stocking densities. The experiment was carried out during the period from 06 August to 22 December 2014. Three stocking densities were used as 125, 250 and 375 fish/dec and designated as treatment T1, T2 and T3 respectively each having two replicates. All the fishes were of same age group having average initial body weight of 1.34g. A commercial feed was supplied at the rate of 40% of the body weight and then gradually it was readjusted to 20%, 10%, 5% and 3% respectively and continued up to the end of the experiment. The water quality parameters were monitored at 14 days interval and the ranges were: temperature 19.34 to 31.40°C, pH 6.83 to 8.03, dissolved oxygen 4.78 to 6.82 mg/l and transparency 29.02 to 49.45cm.The result of the present study showed that the mean weight gain was significantly (P<0.01) highest in T1(120.58g) followed by T2(89.74g) and T3(74.58g).The average specific growth rates (SGR) was 2.590, 2.560 and 2.598 (%/day) in treatment T1, T2 and T3 respectively. There was significant (P<0.01) differences among the survival rate. The survival rate 87% was significantly highest in T1followed by 76% in T2 and 69% in T3.The fish productions were 13.25, 17.30 and 19.64 kg/decimal in T1, T2 and T3 respectively. Although the highest production was obtained in T3 but individually growth performance of monosex tilapia was highest in T1. The highest net profit was found (BDT 3,373.30) inT1compared toT2 (BDT 3,017) and T3 (BDT 2,918). The highest benefit cost ratio (BCR) was 1.79 in T1followed by 1.44 in T2and 1.28 in T3. Based on the result of present experiment, fish farmers might be suggested to rear tilapia at lower stocking density to get higher growth, survival and benefit in a short period of time. Asian J. Med. Biol. Res. September 2016, 2(3): 471-476